PENGUATAN KOMPETENSI DOKTER MELALUI PELATIHAN ADVANCE CODING DIAGNOSE AND PROCEDURE IN CASEMIX INA-CBG DI RUMAH SAKIT ISLAM JAKARTA - Tri Ananto; Nur Asni Gani; Laura Mayanda; Medo Maulianza; Syed Aljunid; Ade Ella Liana (Taksasila Edukasi Insani, 2025)
The JKN program is a government program within the National Social Security System launched on January 1, 2014. The organizer of JKN is BPJS Kesehatan with its provider being hospitals. The payment system used to pay hospitals that have provided health services is INA CBG. The standardization of coding of diagnoses and disease procedures uses international standards, namely ICD 10 and ICD 9 CM. Doctors as the main actors in the provision of health services are given training to improve the competence of doctors in writing the correct diagnosis and procedures for medical observations that occur in patients undergoing treatment. Writing the correct diagnosis and procedures can optimize hospital income. The training was conducted for general practitioners, specialist doctors, Casemix teams, coders, nursing teams, medical records. The training was conducted over 2 days providing the concepts of Casemix, INA-CBG and ICD 10 and ICD 9 CM. Participants used the Code Assist application to discuss hospitals in general and specific cases of the Jakarta Islamic Hospital.Keywords: Diagnosis and Procedures, Indonesia Case Based Groups (INA-CBG), ICD 10 and ICD 9 CM.